Performance evaluation of a solar still using hybrid nanofluid glass cooling-CFD simulation and environmental analysis. (February 2022) - Shoeibi, Shahin; Kargarsharifabad, Hadi; Rahbar, Nader; Ahmadi, Goodarz; Safaei, Mohammad Reza
Abstract: The use of nanopowders in the base fluids dramatically impacts the performance of cooling and heating systems. Nanoparticles enhance thermal conductivity by altering the thermal properties of the base fluid. The purpose of this paper is to numerically evaluate the glass cooling of a double-slope solar still using a hybrid nanofluid (Al2 O3 -TiO2 ) at a concentration of 0.4%. The hybrid nanofluid (Al2 O3 -TiO2 ) glass cooling flows over the glass to decrease the cover temperature and raise the freshwater generation using a pump. Hybrid nanofluid cover cooling raises the temperature difference between evaporation and condensation areas. The use of hybrid nanofluid glass cooling increases the natural convection heat transfer inside the solar still. The convective heat transfer coefficient and constant temperature are considered as boundary conditions of the glass cover and water surfaces of the solar still, respectively. The simulation results revealed that solar desalination's freshwater yield and energy efficiency increased by 11.09% and 28.21%, respectively, when hybrid nanofluid glass cooling is used compared to solar desalination without hybrid nanofluid. The optimal value of nanoparticle concentration was 0.45%, as estimated by the CFD simulation. Also, a new model for estimating the freshwater productivity of solar desalination with hybrid nanofluid glass cooling was developed and verified. Moreover, the environmental and exergoenvironmental parameters in solar desalination with hybrid nanofluid glass cooling were enhanced by 12.45% and 3.71 times, respectively.